Measuring Human Rights and Islamicity of Indonesian Anti-Terrorism Law - Asmawi Asmawi; Yayan Sopyan; Mujar Ibn Syarif; Isnawati Rais (AHKAM : Jurnal Ilmu Syariah, 2019)
This study focuses on the problem of the extent to which human rights and islamicity (Islamic law norms) are accommodated within Indonesian anti-terrorism law (Law No. 5 of 2018). The study uses a qualitative approach with a documentary study in data collection. The result shows that Law No. 5 of 2018 has threatened human rights in some issues. This is indicated by certain matters including arrest, detention, capital punishment, interception, and revocation of citizenship. Meanwhile, the islamicity of Law No. 5 of 2018 is open to interpretation and reinterpretation. The study of measuring human rights and islamicity of Law No. 5 of 2018 has a significant contribution to the substantive implementation of  Islamic criminal law in the context of Indonesianness, as well as modernity, which also means the implementation of Islamic law and human rights at once.